Perlindungan Hukum bagi Masyarakat Hukum Adat Adonara yang Melakukan Perjanjian Gadai Tanah (Gerang Ekan) Tanpa Perjanjian Tertulis - Filgentius Xander Laga; Umbu Yanri Aryanto Fallo; Antonius Revilno Konseng Dacunha; Stefanus Don Rade (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Agreements in Indonesia: Each region has a special name or customary term to describe the agreement, however, each agreement term has the same meaning. Article 1338 of the Civil Code states that